Role of advanced imaging in COVID-19 cardiovascular complications - Catapano, Federica (Insights Imaging, 2021)
Clinical manifestations of COVID-19 patients are dominated by respiratory symptoms, but cardiac complications are commonly observed and associated with increased morbidity and mortality. Underlying pathological mechanisms of cardiac injury are still not entirely elucidated, likely depending on a combination of direct viral damage with an uncontrolled immune activation. Cardiac involvement in these patients ranges from a subtle myocardial injury to cardiogenic shock. Advanced cardiac imaging plays a key role in discriminating the broad spectrum of differential diagnoses. Present article aims to review the value of advanced multimodality imaging in patients with suspected SARS-CoV-2-related cardiovascular involvement and its essential role in risk stratification and tailored treatment strategies. Based on our experience, we also sought to suggest possible diagnostic algorithms for the rationale utilization of advanced imaging tools, such as cardiac CT and CMR, avoiding unnecessary examinations and diagnostic delays.